Perbandingan Kualitas Air Sungai Musi pada Tiga Tata Guna Lahan - Dewi Rosanti; Dewi Novianti; Yunita Panca Putri (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2021)
Research of water quality on Musi river was conducted from April to November 2020, aims to compare the quality of the Musi river water as parameters of chemical, physical and biological in different types of land use. This study used a survey method by determining the sampling of test materials and measuring the water  quality  which carried out by purposive sampling  adjusted to land use. The sampling point for domesticl areas is in the area of Kelurahan 1 Ulu (station 1). The sampling point as  sands mining area is in the area of Tangga Takat Village (station 2). The third land use is in Kelurahan 13 Ulu (station 3). Data analysis in the laboratory includes chemical parameters (DO, COD and BOD), physical (TDS, brightness) and biological based on the content of Escherichia coli bacteria. The results showed that the chemical quality of water in the housing and fish catchment areas generally met class II water quality standards, but did not meet the water quality standards for sand mining areas. Physically, the water quality in the three areas still meets the water quality standards, although the TDS content, temperature range, brightness is not good in the sand mining area. Based on biological parameters, all areas are classified as polluted with E. coli content that is more than 100 individu/ 100 ml of water, so it is not suitable for consumption and requires special handling for use in everyday life.